A childhood acute lymphoblastic leukemia genome-wide association study identifies novel sex-specific risk variants. Issue 46 (November 2016) - Singh, Sandeep K.; Lupo, Philip J.; Scheurer, Michael E.; Saxena, Anshul; Kennedy, Amy E.; Ibrahimou, Boubakari; Barbieri, Manuel Alejandro; Mills, Ken I.; McCauley, Jacob L.; Okcu, Mehmet Fatih; Dorak, Mehmet Tevfik
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Childhood acute lymphoblastic leukemia (ALL) occurs more frequently in males. Reasons behind sex differences in childhood ALL risk are unknown. In the present genome-wide association study (GWAS), we explored the genetic basis of sex differences by comparing genotype frequencies between male and female cases in a case-only study to assess effect-modification by sex. The case-only design included 236 incident cases of childhood ALL consecutively recruited at the Texas Children's Cancer Center in Houston, Texas from 2007 to 2012. All cases were non-Hispanic whites, aged 1 to 10 years, and diagnosed with confirmed B-cell precursor ALL. Genotyping was performed using the Illumina HumanCoreExome BeadChip on the Illumina Infinium platform. Besides the top 100 statistically most significant results, results were also analyzed by the top 100 highest effect size with a nominal statistical significance ( P <0.05). The statistically most significant sex-specific association ( P = 4 × 10 −6 ) was with the single nucleotide polymorphism (SNP) rs4813720 ( RASSF2 ), an expression quantitative trait locus (eQTL) for RASSF2 in peripheral blood. rs4813720 is also a strong methylation QTL (meQTL) for a CpG site (cg22485289) within RASSF2 in pregnancy, at birth, childhood, and adolescence. cg22485289 is one of the hypomethylated CpG sites in ALL compared with pre-B cells. Two missense SNPs, rs12722042 and 12722039, in the HLA-DQA1 gene yielded the highest effect sizes (odds ratio [OR] ∼ 14; P <0.01) for sex-specific results. The HLA-DQA1 SNPs belong to DQA1∗01 and confirmed the previously reported male-specific association with DQA1∗01 . This finding supports the proposed infection-related etiology in childhood ALL risk for males. Further analyses revealed that most SNPs (either direct effect or through linkage disequilibrium) were within active enhancers or active promoter regions and had regulatory effects on gene expression levels. Cumulative data suggested that RASSF2 rs4813720, which correlates with increased RASSF2 expression, may counteract the suppressor effect of estrogen-regulated miR-17-92 on RASSF2 resulting in protection in males. Given the amount of sex hormone-related mechanisms suggested by our findings, future studies should examine prenatal or early postnatal programming by sex hormones when hormone levels show a large variation.